Integrated use of feed additives for fattening rams of Karakul breed (Texas Journal of Multidisciplinary Studies, 2022)
The organization of full-fledged feeding is the main factor in realizing the genetic potential of farm animals. In this regard, the use of effective feed additives in animal feeding can increase the energy and biological usefulness of diets. The main advantage of using complex ingredients is the "effect of complementing each other with nutrients", based on the biological patterns of growth, development and overall metabolism of the animal body. The effect is explained by the fact that the increase in digestibility, digestibility or improvement of metabolic processes is influenced by the presence in diets by nature of different substances, i.e. synergy, which represent energy, mineral or biologically active substances, products of synthetic or microbial synthesis. This article presents the results of stall fattening of karakul baranchiks of 6 months of age using feed additives in the complex: 1) bentonite as a source of minerals; 2) probiotic "Bactovit" for feed purpose as a natural biostimulant; 3) urea, as a source of nitrogen and increasing the protein nutrition of diets for ruminants, 4) suspensions of chlorella algae as a source of biologically active substances. The results are presented by the data of the obtained weight gains of the live weight of experimental animals, feed costs per unit of weight gain, control slaughter and deboning of carcasses.